Sathya Indra's Creative Process in Creating Song: Case Study of the Influence of Social Environment on Creativity in Creating Songs - Septiawan, Dhany; Setiyono, Budi (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
The process of creativity can be interpreted as an activity before the creation of an idea, or a stage before producing a new discovery and finding previously existing relationships. This study aims to reveal the process of creativity carried out by Sathya Indra in creating songs, several studies conducted by previous researchers have discussed more about a creative process that specifically focuses on relying on individual innovation, but in this study tries to describe how the creative process of an individual music artist is influenced by his socio-cultural environment. The approach in this study uses a qualitative descriptive analysis method. This method seeks to answer the challenge of understanding, providing interpretation and empirical phenomena combined with a system of logic and truth values, as well as the applicable context through direct observation. The stages in finding data for this study were observation, interviews, documentation and document studies. Sathya Indra is a young musician who is known by the wider community after creating many songs. In making his songs, Indra gets his ideas and inspiration from social cultures and from what he sees, most of his songs talk about the love life of young people, seeing from the conflicts experienced, from these events Indra gets his creative ideas in making lyrics for his songs. The content of this study includes Sathya Indra's artistic position, stages of creating songs, forms and results of creativity and the influence of the environment on the structure of the song. The conclusion of this study attempts to describe how the creative process of an individual music artist is influenced by the environment.